Assessment of the stability of virgin coconut oil during deep-frying - J. M. N. Marikkar; J. M. M. A. Jayasundara; S. A. H. Prasadika; C. V. L. Jayasinghe; G. A. S. Premakumara (International Coconut Community Journal, 2007)
Virgin coconut oil (VCO) is a unique product out of coconut. Since there is a growing market for VCO in the international trade, information on the frying stability would be useful for producers, traders and end-users. A study was conducted to compare the frying stability of VCO with those of ordinary coconut oil (CNO) and refined corn oil (CO). Each oil sample was placed separately in an electrically operated open fat fryer and heated at 180°C for a period of 8 h. During frying, samples were withdrawn from the fryer at specified time intervals to monitor the changes in free fatty acid (FFA) content, peroxide value (PV), total polar compound (TPC) and anisidine value (AnV) using standard test methods. Experimental results showed that there was a tendency for the increase of FFA, PV, TPC, and AnV of all three oils. However, the values of these parameters corresponding to VCO were found to be lowest through out the 8 h frying operation. Since TPC is used as a reference parameter to determine the rejection point of frying oils, prediction models were developed for TPC using simple regression analysis. Based on the prediction models, the rejection points of VCO, CNO, and CO were found to be 13.45, 10.95, and 10.25, respectively.